Determination of 53 volatile flavor components in strong-flavor Baijiu by gas chromatography - XU Jia, LIAO Li, ZOU Yongfang, GAN Qiao, JING Xiong, PENG Houbo, QIAN Yu (Zhongguo niangzao)
In order to establish an efficient and accurate method for detecting various trace components in strong-flavor (Nongxiangxing) Baijiu, a gas chromatography (GC) method for the detection of 53 volatile flavor components in strong-flavor Baijiu was established by optimizing the column types, split ratio and programmed temperature conditions. The results showed that the optimal GC conditions were as follows: CP-WAX 57 CB capillary column (50 m×0.25 mm×0.2 μm), a split ratio of 40:1, and a programmed temperature (initial temperature 35 ℃ for 5 min, increased at 4 ℃/min to 45 ℃ for 3 min, increased at 8 ℃/min to 140 ℃ for 2 min, then increased at 20 ℃/min to 205 ℃ for 16 min). This method could detect 53 volatile flavor substances in strong-flavor Baijiu within 44 min, achieving good linearity for each component within their respective concentration ranges (R2≥0.998 6). The limits of detection was 0.26-5.09 mg/L, limits of quantification was 0.87-18.97 mg/L, spiked recovery rate was 80.10%-113.21%, and the relative standard deviation for precision tests was 0.25%-2.75%. The results indicated that the method was simple to perform, with a short detection time and good separation performance, and could meet the requirements for detecting main flavor components in strong-flavor Baijiu.